STUDI KASUS: FAKTOR PENDUKUNG DAN PENGHAMBAT IMPLEMENTASI PROGRAM BIMBINGAN INTENSIF OLIMPIADE MADRASAH INDONESIA (OMI) - Amelia Anwaral Maulida; Ahmad Suriyansyah; Arta Mulya Budi Harsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The quality of education in non-urban areas faces many challenges, such as limited resources and a shortage of competent instructors in their fields. However, student achievement in the Indonesian Madrasah Olympics (OMI) is an important focus in improving student competitiveness. This study aims to examine the supporting and inhibiting factors in the implementation of the OMI intensive guidance program and its impact on student achievement at MI Miftahul Ulum Sumber Jaya, a consistently high-achieving non-urban madrasah. This exploratory case study uses qualitative methods. Data were collected through in-depth interviews, non-participatory observation, and document studies in the form of test questions, participant cards, certificates, and championship trophies. The unit of analysis was the implementation of guidance at the madrasah. The results showed that strict selection, structured material reinforcement, increased student motivation, and active collaboration between teachers and parents were the main supporting factors. Obstacles such as limited guidance time and a lack of competent mentors could be overcome through flexible scheduling. This program had a positive impact on increasing student motivation, discipline, and academic achievement in the OMI competition. These findings emphasize the importance of differentiated learning and school-family cooperation in improving the quality of education in non-urban madrasahs. This study provides practical contributions to the development of effective Olympic guidance.